A novel near-infrared II viscosity-responsive probe for surgical fluorescence guidance: laboratory investigation in a murine subcutaneous glioma model - Lin, Lihao; Han, Tianyang; Jiang, Huizhong; Zhang, Yuewei; Guan, Yi (Frontiers in Oncology, 2026)
Distinguishing brain tumor boundaries from surrounding parenchymal tissue with high sensitivity and specificity remains a daunting clinical challenge due to their diffuse nature and proximity to critical brain regions. Currently approved clinical fluorescent contrast agents are insufficient for clearly delineating the margins of gliomas. This study evaluated a novel near-infrared II (NIR-II) viscosity responsive fluorescent probe, POH, for fluorescence guided surgery in glioma models. Compared to commercial dyes, this probe offers advantages such as strong photostability, large Stokes shift, and high responsiveness to tumor tissue. Statistical analysis of postoperative survival and tissue margins demonstrated that the viscosity responsive probe POH exhibited significant advantages over the mainstream NIR contrast agent ICG. The unique chemical structure of this semi-cyanine derivative offers potential advantages for fluorescence guided surgery of gliomas, providing new insights into the design and selection of surgical navigation contrast agents. However, it should be noted that the subcutaneous glioma model used in this study does not replicate the intracranial tumor microenvironment or the impact of the blood-brain barrier. Future studies using orthotopic glioma models are essential to fully evaluate the translational potential of POH.